2008
DOI: 10.1007/s00542-008-0643-y
|View full text |Cite
|
Sign up to set email alerts
|

Failure of electronic devices due to condensation

Abstract: The increasing usage of electronic devices and the progressive trend of miniaturisation in automotive applications require different installation locations. According to varying locations, different climate conditions will occur. In this article, the influence of condensation on the reliability of electronic devices is examined. For the detection of failures or the loss of functionality it is essential to determine the occurrence of condensation. A new microsensor based on the CCCprinciple (condensate controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It has also been 9 Effect of potential bias on a probability of ECM and b dendrite current reported that the threshold electric field under which the ECM will not occur is below 1 mV mm 21 . 4 An increase in electric field widens the precipitation of tin hydroxide, and also promotes the formation of dendrites (Fig. 10b).…”
Section: Effect Of Electric Field On Electrochemical Migrationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been 9 Effect of potential bias on a probability of ECM and b dendrite current reported that the threshold electric field under which the ECM will not occur is below 1 mV mm 21 . 4 An increase in electric field widens the precipitation of tin hydroxide, and also promotes the formation of dendrites (Fig. 10b).…”
Section: Effect Of Electric Field On Electrochemical Migrationmentioning
confidence: 99%
“…At high chloride levels the probability of migration also slightly reduces due to the large amounts of dissolved tin ions in the solution which leads to heavy precipitation reducing the migration rate as reported in literature. 15,22 The precipitated species can be hydroxides of tin namely Sn(OH) 4 and/or -Sn(OH) 2 , although intermediate hydroxyl chloride species are also possible. 23 Optical micrographs of representative tested components with flux residue (Fig.…”
Section: Effect Of Sodium Chloride and Flux Residue On Electrochemicamentioning
confidence: 99%
See 1 more Smart Citation
“…The lifetime and reliability of the electronic devices are important both for the device functionalities and the environmental control. The water intervention to the electronic devices is an important aspect for maintaining and enhancing the device performance 1 , 2 because this type of phenomenon can usually lead to a series of safety issues, sometimes even catastrophes. As silicon is the cornerstone for electronic devices, the performance of most of the electronic devices can be deteriorated by the moisture/steam/ice on silicon inevitably in many scenarios even with the device insulation in place, thus causing short-circuiting, reduced sensitivity or even failure of sensors, such as those used in high-temperature production environments or polar developments.…”
Section: Introductionmentioning
confidence: 99%
“…This implies the formation of an electrolyte solution and the increase in the conductivity of the moisture film on the PCBA surface. As a consequence, the resulting increase in LC can compromise the function of electronic devices [9].…”
Section: Introductionmentioning
confidence: 99%